Biomimetic assembly to superplastic metal–organic framework aerogels for hydrogen evolution from seawater electrolysis. Issue 2 (23rd September 2021) - Sun, Yuntong; Xu, Shuaishuai; Ortíz‐Ledón, César A; Zhu, Junwu; Chen, Sheng; Duan, Jingjing
Abstract: Applications for metal–organic frameworks (MOFs) demand their assembly into three‐dimensional (3D) macroscopic architectures. The capability of sustaining structural integrity with considerable deformation is important to allow a monolithic material to work reliably. Nevertheless, it remains a significant challenge to introduce superplasticity in 3D MOF networks. Here, we report a general procedure for synthesizing 3D superplastic MOF aerogels inspired by the hierarchical architecture of natural corks. The resultant MOFs exhibited excellent superplasticity that can recover fully and rapidly to its original dimension after 50% strain compression and unloading for >2000 cycles. The 3D superplastic architecture is achieved by successively assembling one‐dimensional (1D) to two‐dimensional (2D) and then 3D, in a variety of MOFs with different transition metal active sites (Co‐, NiMn‐, NiCo‐, NiCoMn‐) and organic ligands (2‐thiophenecarboxylic acid and glutaric acid). Latent applications have been demonstrated for NiMn‐MOF aerogels to serve as a new generation of flexible electrocatalysts for hydrogen evolution reaction (HER) from seawater splitting, which requires a low overpotential of 243 mV to achieve a current density of 10 mA·cm −2 . Notably, the electrocatalyst remains stable even being deformed, as the overpotential to achieve a current density of 10 mA·cm −2 increases slightly to 270, 264, and 258 mV after one‐, two‐, and threefold, respectively. In great contrast, traditional MOF powder‐electrodes demonstrate significant activity decay under similar conditions. This work opens up enormous opportunities for exploring new applications of MOFs in a freestanding, structurally adaptive, and macroscopic form. Abstract : Superplastic metal–organic framework (MOF) assembled macroscopic architecture is reported for the first time, which can fully and rapidly recover to its initial states after 50% strain compression and unloading for 2000 cycles. The facile synthetic strategy has been extendable to many other single‐, binary‐, and ternary‐metal MOF assemblies. The NiMn‐MOF aerogel could serve as a novel class of flexible electrode for efficient hydrogen evolution reaction (HER) from natural seawater.